National Athletic Trainers` Association Position Statement: Fluid replacement for athletes - Casa, D. J.; Armstrong, L. E.; Hillman, S. K.; Montain, S. J.; Reiff, R. V.; Rich, B. S.; Roberts, W. O.; Stone, J. A. (Journal of Athletic Training, 2000)
Objective: To present recommendations to optimize the fluid-replacement practices of athletes. Background: Dehydration can compromise athletic performance and increase the risk of exertional heat injury. Athletes do not voluntarily drink sufficient water to prevent dehydration during physical activity. Drinking behavior can be modified by education, increasing accessibility, and optimizing palatability. However, excessive overdrinking should be avoided because it can also compromise physical performance and health. We provide practical recommendations regarding fluid replacement for athletes.